Diffusion of Nitrogen in Ti-13V-11Cr-3Al Alloys - Grandini, Carlos Roberto [UNESP]; Kamimura, Emerson Haruiti [UNESP]; Severino Martins, Jose Roberto [UNESP]; Zschommler Sandim, Hugo Ricardo; Florencio, Odila (Trans Tech Publications Ltd, 2009)
Metals with a bcc crystalline structure such as Ti-13V-11Cr-3Al alloys have their physical properties significantly changed through the addition of interstitial elements such as oxygen and nitrogen. These metals can dissolve substantial amounts of interstitial elements forming solid solutions. Mechanical spectroscopy measurements constitute a powerful tool for studying interactions of these interstitial elements with other elements that make up the alloy. From these measurements, it is possible to obtain information regarding diffusion, interstitial concentration, interaction between interstitials, and other imperfections of the crystalline lattice, In this paper, Ti-13V-11Cr-3Al alloys with several amount of nitrogen, in a solid solution, were studied using mechanical spectroscopy (internal friction) measurements. The results presented complex internal friction spectra which were resolved in a series of constituent Debye peaks corresponding to different interactions and interstitial diffusion coefficients. Pre-exponential factors and activation energies were calculated for nitrogen in theses alloys.
Keywords: Diffusion; Ti alloys; Mechanical Spectroscopy; Nitrogen